Botulism outbreak in cattle due to ingestion of accidental deteriorated feed - Milena Carolina Paz; José Tiago Roza de Moraes; Franciéli Adriane Molossi; Andressa da Silva Martins; Tamires Ataides Silva; Luciane Oliveira Marques; Ananda Paula Kowalski; Ana Carolina Borsanelli; Welden Panziera; David Driemeier (Ciência Rural)
ABSTRACT: Botulism is a condition caused by the ingestion of pre-formed toxins produced by the bacterium Clostridium botulinum. This study described an outbreak of type D botulism with a high mortality rate (67%) in a cattle herd, caused by the consumption of fermented silage. The affected cattle presented with a hyperacute to acute clinical course with progressive flaccid paralysis. Five animals underwent necropsy with no significant macroscopic and microscopic alterations. A most probable source of contamination was deemed to be an inadequately stored silage; although, the toxin was not detected in the feed. The diagnosis of botulism was based on both clinical and epidemiological findings and the detection of botulinum toxin in the intestinal contents of two of the affected cattle. The present study emphasized the high number of fatally affected cattle, an unusual source of botulinum toxin and the importance of proper management of animal feed supply.